No differences between RAI of less than 15 mCi or 15 mCi for Thyrotoxicosis: A Universiti Kebangsaan Malaysia Medical Centre (UKMMC) experience - Shahar, Mohammad Arif; Omar, Ahmad Marzuki; Ab Aziz, Aini; C P, Ooi; AR, Anilah; M., Azura Dina; Zainuddin, Suehazlyn; Abd Wahab, Norasyikin; Mustafa, Norlaila; Sukor, Norlela; Kamaruddin, Nor Azmi (ASEAN Federation of Endocrine Societies, 2013)

(untitled)
Background: Radio-ablative iodine (RAI) is one of the treatment of choice for thyrotoxicosis. This study was done to compare the rate of remission in thyrotoxic patients who received either low dose radio-active iodine-131 (RAI) (10 or 12 mCi) and higher dose RAI (15 mCi). Methods: This was a retrospective analysis of 69 thyrotoxic patients who received RAI therapy from January 2011 until December 2011 in UKM Medical Centre. They were followed up for a period of two years. Data was analyzed using SPSS v.20. Results: Sixty-nine patients underwent RAI in the year 2011. Fifty-five patients received either 10 or 12 mCi and 14 patients received 15 mCui radio-iodine. There were no difference between the characteristics of patients in both groups in terms of age, gender, ethnicity, and thyroid stimulating hormone (TSH) level prior to the RAI, and thyroid antibodies (anti-thyroglobulin and anti-thyroid peroxidase). Those who received higher dose RAI have higher median thyroxine level prior to RAI [(34.7(24.4-52.8) vs. 26.1(16.6-34.6) pmol/L). Using lower RAI dose (<15 mCui) was not associated with the need for a second RAI. The rate of remission was the same between the 2 groups at 6 months. Although there was higher remission rate in the lower RAI dose group (65.1% vs. 50.0%) at 12 months, it was statistically not significant (p=0.634). At 24 months, there was no difference in remission rate between the two groups, with more than 80% of the patients had undergone remission. Conclusions: There was no difference in terms of rate of remission at 6 months, 12 months and 24 months between those who received low and higher dose RAI therapy.